Diversity of susceptible hosts in canine distemper virus infection: a systematic review and data synthesis. Issue 1 (December 2016) - Martinez-Gutierrez, Marlen; Ruiz-Saenz, Julian
Abstract Background Canine distemper virus (CDV) is the etiological agent of one of the most infectious diseases of domestic dogs, also known as a highly prevalent viral infectious disease of carnivores and posing a conservation threat to endangered species around the world. To get a better panorama of CDV infection in different Orders, a retrospective and documental systematic review of the role of CDV in different non-dog hosts was conducted. The bibliographical data were collected from MedLine/PubMed and Scopus databases. Data related to Order, Family, Genus and Species of the infected animals, the presence or absence of clinical signs, mortality, serological, molecular or antigenic confirmation of CDV infection, geographic location, were collected and summarized. Results Two hundred seventeen scientific articles were considered eligible which includes reports of serological evaluation, and antigenic or genomic confirmation of CDV infection in non-dog hosts. CDV infects naturally and experimentally different members of the Orders Carnivora (in 12 Families), Rodentia (four Families), Primates (two Families), Artiodactyla (three Families) and Proboscidea (one Family). The Order Carnivora (excluding domestic dogs) accounts for the vast majority (87.5 %) of the records. Clinical disease associated with CDV infection was reported in 51.8 % of the records and serological evidence of CDV infection in apparently healthy animals was found in 49.5 % of the records. High mortality rate was showed in some of the recorded infections in Orders different to Carnivora. In non-dog hosts, CDV has been reported all continents with the exception of Australasia and in 43 different countries. Conclusions The results of this systematic review demonstrate that CDV is able to infect a very wide range of host species from many different Orders and emphasizes the potential threat of infection for endangered wild species as well as raising concerns about potential zoonotic threats following the cessation of large-scale measles vaccination campaigns in the human population.